Elevated Cell-Free DNA Measured by a Simple Assay Is Associated With Increased Rate of Colorectal Cancer Relapse. Issue 6 (5th June 2016) - Czeiger, David; Shaked, Gad; Sebbag, Gilbert; Vakhrushev, Alex; Flomboym, Anatoly; Lior, Yotam; Belochitski, Olga; Ariad, Samuel; Douvdevani, Amos
Abstract : Objectives: For patients with early stage colorectal cancer (CRC), markers of high-risk relapse are needed. In a previous study on 38 randomly selected patients with CRC, we found good correlation between presurgery cell-free DNA (CFD) concentrations and standard prognostic factors. In the current study, we revisited the same patients at 5-year survival, aiming to evaluate the predictive power of presurgery CFD levels. Methods: We revisited 38 patients with CRC previously analyzed for 5-year outcome. CFD was measured using a simple fluorescent assay that we developed. Results: All recurrent patients and patients who had died of cancer within 5 years were shown to have presurgery CFD values above 800 ng/mL. The negative predictive value for cancer-related disease was 100%. Cox regression analysis for disease-free survival showed a hazard ratio of 6.03 ( P = .003) for CFD, which was higher than the ratio of the disease stage, 1.9 ( P = .006). The survival-free curve of stage I and II patients with elevated CFD was significantly different from patients with normal levels ( P = .0136); 5 (41.7%) of 12 patients had died of cancer or had experienced a recurrence. Conclusions: CFD may possibly be a decisive criterion to identify patients with local disease who might benefit from adjuvant chemotherapy.